2005
DOI: 10.1109/jsen.2004.841429
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of CMOS pseudoactive pixel sensor (PAPS) structure for low-dark-current and large-array-size imager applications

Abstract: In this paper, a pixel structure called the optimal pseudoactive pixel sensor (OPAPS) is proposed and analyzed for the applications of CMOS imagers. The shared zero-biased-buffer in the pixel is used to suppress both dark current of photodiode and leakage current of pixel switches by keeping both biases of photodiode and parasitic pn junctions in the pixel bus at zero voltage or near zero voltage. The factor of photocurrent-to-dark-current ratio per pixel area (PDRPA) is defined to characterize the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…8. Its fill factor is 59% which is comparable of PAPS in [26] (with pixel size almost 4 times bigger) but larger than 42% of OPAPS in [27].…”
Section: Zero Bias Pixel Sensor (Zbps)mentioning
confidence: 76%
See 2 more Smart Citations
“…8. Its fill factor is 59% which is comparable of PAPS in [26] (with pixel size almost 4 times bigger) but larger than 42% of OPAPS in [27].…”
Section: Zero Bias Pixel Sensor (Zbps)mentioning
confidence: 76%
“…Although each leakage current is only a tiny fraction of the photocurrent, its effect becomes pronounced when there is a large number of pixels connected to a column. In [27], it is suggested that one ZCBDI should be shared with only 4 PAPS pixels, called OPAPS. This results is using more than one ZCBDI per column and effectively reduces the fill factor down to 42% for a 352x288 pixel array.…”
Section: Pseudo-active Pixel Sensor (Paps)mentioning
confidence: 99%
See 1 more Smart Citation